Field effects on spontaneous magnetization reversal of bulk BiFe0.5Mn0.5O3, an effective strategy for the study of magnetic disordered systems. (30th June 2015) - Delmonte, Davide; Mezzadri, Francesco; Pernechele, Chiara; Gilioli, Edmondo; Calestani, Gianluca; Cabassi, Riccardo; Bolzoni, Fulvio; Spina, Gabriele; Lantieri, Marco; Solzi, Massimo
Abstract: We report a comprehensive study of the spontaneous magnetization reversal (MRV) performed on the disordered polycrystalline perovskite BiFe0.5 Mn0.5 O3, an intriguing compound synthesized in high pressure–high temperature conditions. In disordered systems, the origin of MRV is not completely clarified, yet. In BiFe0.5 Mn0.5 O3, compositional disorder involves the ions on the B-site of the perovskite determining the presence of mesoscopic clusters, characterized by high concentrations of iron or manganese and thus by different resultant magnetization. This leads to the observation of two singular fields H 1 and H 2 dependent on the degree of inhomogeneity, unpredictably changing from sample to sample due to synthesis effects. These fields separate different magnetic responses of the system; for applied fields H < H 1, the Fe and Mn clusters weakly interact in a competitive way, giving rise to MRV, while for an intermediate field regime the energy of this weak interaction becomes comparable to the energy of the system under field application. As a consequence, the zero field cooled magnetization thermal evolution depends on the sample degree of inhomogeneity. In this field regime, applied field Mössbauer spectroscopy indicates that the iron rich clusters are highly polarized by the field, while the largest part of the material, consisting of AFM clusters characterized by axial anisotropy and uncompensated moments, shows soft or hard magnetism depending on T . Above the higher singular field, the M ( T ) curves show the trend expected for a classical antiferromagnetic material and the competitive character is suppressed. The MRV phenomenon results to be highly sensitive on both the thermal and magnetic measurement conditions; for this reason the present work proposes a characterization strategy that in principle has a large applicability in the study of disordered perovskites showing similar phenomenology.